NK cell immunopotentiators-loaded nanoliposomes enhance ADCC effect for targeted therapy against HER2-positive breast cancer - Ruoxin Du; Changqing Cao; Dong Fan; Guodong Li; Shuangpeng Pu; Xinyao Xu; Mengmeng Liu; Gege Shi; Yuxin Wu; Qiang Hao; Yuan Gao; Juliang Zhang; et al. (Cell Communication and Signaling)
Abstract Trastuzumab serves as a cornerstone of first-line therapy for HER2-positive (HER2+) breast cancer; however, a significant challenge arises due to the emergence of resistance within approximately one year of commencement of treatment, particularly in advanced cases with metastatic disease where its efficacy is limited. Our investigation into the tumor tissue from HER2+ breast cancer patients, employing single-cell sequencing and bioinformatics analysis, has elucidated a crucial mechanism underlying the reduced responsiveness of tumors to trastuzumab: the diminished infiltration and activity of natural killer (NK) cells within the tumor microenvironment (TME). To counteract this impediment, we meticulously selected two potent immune-modulating peptides TKD and IP-10p, which are known to recruit and enhance the activity of NK cells. Through in vitro experiments, we substantiated that bolstering the tumor infiltration and activity of NK cells can lead to an enhanced antibody-dependent cell-mediated cytotoxicity (ADCC) effect, thereby amplifying the anti-tumor activity of trastuzumab. Building upon this foundational discovery, we further designed HER2-targeted pH-sensitive nanoliposomes to encapsulate TKD and IP-10p peptides. The novel designed nanoliposomes were strategically employed in conjunction with NK cell supplement therapy within a HER2+ breast cancer model undergoing trastuzumab treatment, yielding a striking anti-tumor response and indicating that the combination strategy effectively reinvigorated the anti-tumor immune response. In essence, this study not only underscores a critical link between the diminished ADCC effect mediated by trastuzumab and the development of resistance in HER2+ breast cancer but also demonstrates leveraging HER2-targeted nanoliposomes to deliver NK cell immunopotentiators can significantly enhance the functional activity of NK cells and their infiltration within the TME, culminating in improved antitumor efficacy of trastuzumab through the augmentation of the ADCC effect. Graphical abstract